Designing novel multilayered nanocomposites for high-performance coating materials with online strain monitoring capability - Anwar Ali, Hashina Parveen (2021)
Multilayered nanocomposites, known for its mechanical properties of very high flow strength, ultra-light weight and stable plastic flow to large strains, represent a class of novel composite nanomaterials in which there arises rare opportunities to design new materials from the ground up and to tailor their properties to suit exactly their performance requirements. These materials can withstand very high strains in the elastic regime without any inelastic relaxation due to plasticity or fracture compared to its bulk counterparts. This extended elastic regime opens up new possibilities for tuning the physical and chemical properties of materials as well as bringing novel functionalities, such as high performance coating materials with online strain monitoring capability. Our resistivity measurements during ex situ uniaxial micropillar compression in this article suggests basic feasibility of a Cu–Nb multilayered nanocomposite with 20 nm layer thickness having a novel functionality for online strain monitoring capability, in addition to its more known application as a high performance coating materials due to its extraordinary strength and deformability. A linear trend of resistivity with respect to true strain for strains in excess of 3.5% was observed and suggests a significant regime for use for strain sensor/detection/monitoring capability.